FIGURATIVE LANGUAGE IN“THE SHAWSHANK REDEMPTION” MOVIE BY FRANK DARABONT - Zuliana Lestari (ELTE Journal (English Languange Teaching and Education), 2020)
This research deals with figurative language in “The Shawshank Redemption” movie by Frank Darabont. This research is a descriptive qualitative study. It is aimed to identify the figurative language found in The Shawshank Redemption movie. In data collection, the research employed triangulation that presented three different techniques, namely documentation, observation, and interview. Based on the findings, it is shown that there were 60 data of comparative figurative language, which consisted of 11 personifications, 18 similes, 24 metaphors, and seven euphemisms. Fiftycontradictivefigurativelanguages were also found. It consisted of 25 hyperboles, one litotes, two oxymorons, two paradoxes, one irony, and 19 sarcasms. Then, 48 Correlative Figurative Language occurred in the movie, which consisted of six allusions, six metonymies, 31 ellipses, and five synecdoches. Lastly, figurative repetition or enforcement occurred 24 times in the movie. They were 21 repetitions, one assonance, one rhetoric, and one pleonasm.